“São João de cores, esse show vai começar!”: gênero, sexualidade e vivências LGBTQI+ no contexto da festa junina cearense - Castro, Thiago Silva de (2023)
The square dance groups are today one of the main cultural manifestations of the state of Ceará/Brazil. They are present in all regions of the state, mobilizing people, especially young people, around the symbols of the traditional June festivals, a popular festivity that has great capillarity in the Northeast region of Brazil, but which is present with great strength throughout the national territory. Mobilizing in a very recurrent way the social imaginaries about a rural Northeast, a discursive invention consolidated over countless decades, the Ceará June Festivities, exemplified especially by the square dance groups, also articulate representations of gender and sexuality anchored in a normative binarism that, in the act of reifying hegemonic performativities of femininity and masculinity, have as an effect the imagetic-discursive naturalization of heterosexuality and cisgenerism as power devices. The research presented here reflects a long-standing relationship between its author and the universe of June festivals in the Brazilian state of Ceará, with special focus on the context of the festivities that take place in the city of Sobral, located in the northern region of this state. The content of this thesis, however, is the result of ethnographic work carried out between 2020 and 2022 in different dimensions that constitute the so-called "June movement in Ceará", starting from the daily life of the square dance groups, but also going through broader instances of this popular celebration, which directly impact the production and consolidation of knowledge about this cultural manifestation in the state and beyond. Although the cultural event discussed here is strongly based on a normative discourse of gender and sexuality, the results of this research indicate significant points of tension in relation to the production of meaning about this popular expression, since it is possible to verify a very expressive presence of individuals with experiences of gender and sexuality different from the cis-heteronorm in the context of the square dance groups, and it is even possible to glimpse a protagonism of LGBTQI+ people in the very being/doing of this popular festivity nowadays. By looking at the experiences of LGBTQI+ people in the universe of traditional June festivals in Ceará, the research identifies that the imagetic-discursive representations and the performativities of gender and sexuality that are expressed in this context are woven in a more complex field than that mobilized by the official narratives that seek to ground the meaning of this popular festivity.